The hemodynamic paradox as a phenomenon triggering recurrent reflux in varicose vein disease - Recek, Cestmir (The International journal of angiology, 2012)
A curious hemodynamic phenomenon emerging as a consequence of the treatment of varicose veins can offer a reasonable explanation why varicose vein and reflux recurrences occur tenaciously irrespective of the applied therapeutic procedure. Saphenous reflux is the most important hemodynamic factor in varicose vein disease: it is responsible for the hemodynamic disturbance, ambulatory venous hypertension, clinical symptoms, and chronic venous insufficiency. Abolition of saphenous reflux eliminates the hemodynamic disturbance and restores physiological hemodynamic and pressure conditions, but at the same time it unavoidably evokes a pressure difference between the femoral vein and the incompetent superficial veins in the thigh during calf pump activity. The pressure difference increases flow and enhances fluid shear stress on the endothelium in pre-existing minor communicating channels between the femoral vein and the saphenous system in the thigh, which triggers release of biochemical agents nitride oxide and vascular endothelial growth factor; the consequence is enlargement (vascular remodeling) of the communicating channels, and ultimately reflux recurrence. Hence, the abolition of saphenous reflux creates preconditions for the comeback of the previous pathological situation. This phenomenon-starting the same trouble while fixing the problem-has been called hemodynamic paradox; is explains why varicose vein and reflux recurrence can occur after any mode of therapy.
Keywords: varicose vein recurrence; venous hemodynamics; hemodynamic paradox